Falas insubmissas: memória e comunicação na obra da escritora Conceição Evaristo - Gomes, Elisângela (2019)
The black literature claims a narrative starred by the black authorship, and in this way, proposes a new form of conceiving the writing and the history of the black population through the Diaspora. By telling this history from the point of view of black people's life experience, they become the subject and not anymore an object, diverging from the stigmatized representations that circulate in the hegemonic literature and also in the mass communication media. The Theory of Communicative Action (TAC) proposed by Jürgen Habermas is based on a cooperative process of interpretation, in which the participants refer themselves simultaneously to something in the objective world, in the social world and in the subjective world, establishing interpersonal relationships and the expression of experiences. The concept of Communicative Action presupposes the language as a way of comprehension and a reflex of the actor’s relations with the world generating reciprocity in the linguistics interactions and in the cultural traditions. Therefore, We proposed to analyze the potential in the literary narrative of the writer Conceição Evaristo whilst Communicative Action, through the book Becos da Memória (2017). The research’s approach had a qualitative nature of the kind bibliographic research. The collection technique utilized was the Semiotics of Culture in Yuri Lótman’s (1979) perspective, crossed by the Theory of Communicative Action (TAC) brought up by Jürgen Habermas (1981; 1989; 1990). The data analysis was made by the selection of fragments of the literary work Becos da Memória (2017), from Conceição Evaristo, that deal with memory and ancestry. The conceptual discussions permeate the fields of literature and communication as mechanisms for the construction of citizenship. Triggering the understanding of escrevivência, concept critical-literary proposed by Conceição Evaristo (1996), to think a communication conceived by the writing of the lived. It is concluded that the creation of a common space for dialogue that propitiate the sharing of the symbolic materialize the Communicative Action as proposed by Habermas. The discursive strategies analyzed demonstrate the potential in (re)assemble a past with origins in Africa, by triggering African civic values that make the diasporica experience positive and point towards the appreciation of the collective life experiences. The materialized memory in the construction of a counter hegemonic literature makes possible the increase of consciousness and the claim of a history that was silenced by the several mechanisms of oppression and deletion.